Medical and orthopedic conditions and sports participation - Diokno, E.; Rowe, D. (Pediatric Clinics of North America, 2010)
The presence of certain medical or orthopedic conditions need not preclude adolescents from being physically active and participating in sports. The benefits of continued physical activity far outweigh any concerns for potential complications for most such conditions. This article reviews sport participation guidelines for adolescents with conditions that include juvenile chronic arthritis, eye injures, solitary kidney, skin conditions, scoliosis, and spondylolysis.